Thermal stabilities and properties of equilibrium phases in the Pt-Te-O system. (March 2017) - Tesfaye, Fiseha; Sukhomlinov, Dmitry; Lindberg, Daniel; Taskinen, Pekka; Akdogan, Guven
Highlights: Maximum thermal stability of PtTe in air was determined to be T  = (603 ± 1) K. Eutectic temperature in the phase region PtTe-Pt was determined to be T  = (1146.6 ± 5) K. At x (Te) = 0.4 and x (Pt) = 0.6, the liquidus temperature was determined to be T  = (1175.2 ± 5) K. Δm H ° (PtTe→L)  = (4.57 ± 0.1) kJ mol −1 was determined for PtTe in equilibrium with Pt-rich liquid. Phases in the Pt-Te-O system were investigated, and a ternary phase diagram was proposed. Abstract: Oxides and intermetallic phases in the platinum-tellurium-oxygen system have been studied. Thermal stabilities, thermodynamics, and structures of the phases reported in the literature, including the conditions under which PtOx form and decompose, have been compiled and critically evaluated. Heat capacities of the binary phases have been estimated, and compared with the scarcely available experimental literature data. The estimated values are generally in agreement with the few available literature data. The intermetallic phase PtTe was synthesized, and thermally analysed by the differential scanning calorimetry and thermogravimetry techniques, under both inert and oxidizing conditions. Based on the calorimetric measurements, the solidus and liquidus temperatures, and enthalpy of melting of PtTe in the phase region PtTe-Pt have been determined. For the first time, the maximum thermal stability of PtTe in an oxidizing atmosphere, close to the partial pressure of oxygen in air, is experimentally determined to be T  = (603 ± 1) K, above which it oxidizes to form TeO2 and Pt. Based on experimental observations in this work combined with the literature review, isothermal ternary phase diagram of the Pt-Te-O system is proposed.